NYIT Energy Advisory Service initial evaluation report - Tenen, G. B. (New York Inst. of Tech., Old Westbury (USA). Center for Energy Policy and Research, 1977)
The Center for Energy Policy and Research of the New York Institute of Technology has organized an ENERGY ADVISORY SERVICE for information dissemination on energy conservation techniques to various target audiences in the New York, New Jersey, and Connecticut area. The Service, in operation since June 1, 1976 established four channels of communication to disseminate energy conservation information and technical assistance: The NYIT Energy Hot Line, the NYIT/ERDA (MRC-TV) Energy Management Seminar program, the Energy Information Center, and the Referral Service. The purposes of this report are two-fold: (1) to provide expanded and up-dated information on operating experiences associated with the NYIT Energy Hot Line and the NYIT/ERDA (MRC-TV) Energy Management Seminar Program, and (2) to provide recently analyzed data emerging from a study designed to investigate the two channels for their absolute and comparative effectiveness in energy technology transfer. Specifically research was designed to cast light on the following questions: (a) in terms of demographics and prior energy attitudes, what kinds of people tend to use the hot line or be drawn to the television seminar; (b) how did channel users feel about the channel after experiencing it; (c) how did channel users perform on energy-transfer effectiveness measures of knowledge and intention to act; and (d) was there any relationship between performance or effectiveness measures and selected demographic and attitudinal variables associated with channel users.